Elevating the Bioactive Potential of Strawberries with Apple Pomace Extract-Infused Chitosan Edible Coating - Luna Maslov Bandić; Marko Vuković; Dora Gavranić; Irina Tanuwidjaja; Mirna Mrkonjić Fuka; Boris Duralija; Slaven Jurić (Polish Journal of Food and Nutrition Sciences)
Postharvest shelf life has always been one of the main shortcomings in the cultivation of perishable fruit, of which strawberries are one of the most important. Hence, this study aimed to maintain the postharvest quality of fully ripe strawberries with the utilization of sustainable and edible coatings made of chitosan and chitosan infused with apple pomace extract. Fruit quality was assessed on days 0, 2, 4, and 9 following the treatment. A sensory evaluation was also performed on day 0 and day 4 and this included visual (freshness, color and glossiness) and organoleptic traits (hardness, texture, flavor, juiciness and sugar/acid ratio perception). Overall, the coating application resulted in the fruit quality improvement in terms of bioactive compound contents and antioxidant capacity. Furthermore, a decrease was recorded in the number of yeasts and moulds, and in the aerobic mesophilic count. Most differences were recorded on days 4 and 9 when the juice of treated strawberries had significantly higher contents of total phenolic compounds, total flavonoids and total anthocyanins, as well as antioxidant capacity. The total anthocyanin content and total flavan-3-ol content determined in the residue after juice separation were also maintained throughout the storage period. Sensory evaluation tests conducted on day 4 resulted in coated strawberries rated with higher scores for all of the sensory parameters when compared to the control.